PREDIKSI EROSI, KLASIFIKASI KEMAMPUAN LAHAN DAN ARAHAN PENGGUNAAN LAHAN DI KECAMATAN BATURITI KABUPATEN TABANAN PROVINSI BALI - Suarsana, I Wayan; Merit, I Nyoman; Sandi Adnyana, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2016)
Land resource damage caused by the land conversion and land use without regard to principles of conservation of soil and water. The damage resulted in the erosion is very high. Changes in land use without regard to principles of conservation of soil and water is currently happening in Baturiti District. Given this research can determine the level of erosion, soil and water conservation planning, land capability classification and proposed land use in Baturiti District. Erosion prediction using USLE (Universal Soil Loss Equation) to estimate the rate of erosion and also to get an idea the determination of soil and water conservation measures appropriate to the region. Determination of the land capability classification method Arsyad (1989) is by classifying land capability to classify land capability class based on the value of the limiting factor of land that is adjusted with land capability classification criteria. Determining of the proposed land use using the scoring method by combining the slope factor of the field, the soil sensitivity of the against erosion and the intensity of daily rainfall. Soil sampling is done by taking a total of 19 soil samples from a unit of land. The prediction results on each unit of land erosion in the area showed the level of erosion is very light covering an area of 11,70 ha, mild erosion area of 5.221,56 ha, erosion was an area of 88,10 ha, severe erosion area of 616.20 ha and very severe erosion area of 2.195,39 ha. Soil and water conservation measures required on land units with erosion prediction value exceeds the value erosion that can be tolerated so that the value could be below the value erosion erosion can be tolerated. Capability classification of the land in the study area consists of land capability class II with an area of 1489,39 ha, class III area of 827,39 ha, class IV with an area of 830.15 ha, class VI area of 1.373,79 ha, class VII covering 1.453,92 ha, class VIII covering an area of 2.176,31 ha. Tutorial use of land for the forest department is directed to the protected forest area covering an area of 2.458,00 ha. Tutorial use of land outside the forest area to protected area 1079.81 ha (13,27%), a buffer zone covering an area of 1.662,31 ha, annual crop cultivation area covering an area of 844.86 ha and seasonal crops cultivation area covering an area of 2.087,97 ha.
Keywords: erosion; land capability; classification; proposed land use.